Influence of casting heterogeneities on microstructure and mechanical properties of austempered ductile iron (ADI) - Boneti,Ludiere Lucas Toldo (2017)
ABSTRACT An investigation was carried out to examine the influence of as-cast heterogeneities on the resulting microstructure and mechanical properties of an austempered ductile cast iron (ADI). A commercial hypereutectic ductile iron alloy with 3.59% C, 2.68% Si, 0.24% Mn and 0.46% Cu (in wt. %) was produced in a coreless induction furnace. The specimens were obtained by casting the alloy into Y-block molds. The austempering heat treatments consisted of pre-heating at 500°C, followed by austenitizing step at 900°C and 930°C during 60 minutes. Austempering was carried out in molten metal baths at temperatures of 300°C and 370°C for 30 minutes. Microstructural characterization was carried out by light optical microscopy (LOM) with image analysis, scanning electron microscopy (SEM-FEG) and X-ray diffraction with Rietveld refinement. The mechanical properties were evaluated by tensile and Vickers hardness tests. The results of this investigation indicate that as-cast heterogeneities have a detrimental effect on the transformed microstructure and mechanical properties of ADI. During austempering, non uniform distribution of graphite nodules and segregation of alloying elements at cell boundaries resulted in transformation gradients throughout the metallic matrix. Intercellular regions displayed inhomogeneous microstructures containing eutectic carbides and martensite. Yield strength, tensile strength and hardness decrease for increasing austempering temperature. Fracture surfaces showed a rapid transition from ductile to cleavage mode at intercellular regions, containing solidification carbides.